Examination of Decision Making and Botched Lethal Injection Executions in Texas. (November 2020) - Harmon, Talia Roitberg; Cassidy, Michael; Kloch, Richelle
This research examines the influence of lethal injection drug shortages on Texas criminal justice officials' decision to change the state's three-drug lethal injection protocol to the use of pentobarbital as a single drug protocol, without judicial oversight. We analyze data collected under the three- and one-drug protocols from 1982 through 2020 and compare differences in the length of time the lethal injection took, and complications reported by media witnesses. Findings suggest a higher rate of botched executions under the one-drug protocol than the three-drug protocol. We discuss the role compounding pharmacies may play in our results, the impact of this work on the U.S. Supreme Court's death penalty jurisprudence, and implications concerning the unilateral decision making by Texas state officials.